The Influence of TikTok Social Media on the Moral Character (Akhlakul Karimah) of Elementary School Students: Pengaruh Media Sosial Tiktok terhadap Akhlakul Karimah Peserta Didik Sekolah Dasar - Azmi Hofifah Hofifah; Ani Nur Aeni; Aah Ahmad Syahid (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2025)
Social media growth influences character formation among primary school students. This study examined the association between TikTok use intensity and students’ akhlakul karimah at SDN Leuwi Bandung 2. A quantitative associational design was applied to 71 fourth- and fifth-grade students selected via proportionate stratified random sampling. Data were gathered using validated and reliable Likert-scale questionnaires and analyzed with descriptive statistics, Pearson correlation, and simple linear regression. TikTok use intensity was high (mean = 32.15), while akhlakul karimah was moderate (mean = 21.62). A strong, significant negative correlation emerged between the variables (r = −0.755; p < 0.001). The regression model Y = 38.175 − 0.515X with R² = 0.57 indicates that 57% of the variance in akhlakul karimah is explained by TikTok use intensity. The findings underscore the need to strengthen digital literacy, parental mediation, and school-based character education to align social media engagement with akhlakul karimah in primary education.